Genome-wide chromosomal instability by cell-free DNA sequencing predicts survival in patients with metastatic breast cancer - Hongnan Mo; Xiaobing Wang; Fei Ma; Ziliang Qian; Xiaoying Sun; Zongbi Yi; Xiuwen Guan; Lixi Li; Binliang Liu; Binghe Xu (Breast, 2020)
Background: Genome-wide chromosomal instability, instead of specific somatic mutations or copy-number alterations in selected genes, is a significant property of cancer and may suggest a new strategy for treatment. Here we utilized cell-free DNA (cfDNA) sequencing to display the whole picture of chromosomal instability in patients with metastatic breast cancer (MBC), and evaluate its predictive value for patient survival. Methods: The clinical data of 65 patients who had frozen plasma and planned to change the therapeutic regimen were retrospectively enrolled. Low-coverage whole-genome sequencing of cfDNA was performed to generate the chromosomal instability represented by chromosomal instability (CIN) score. Results: Tumors with diverse status of hormone receptor and HER2 represented diverse chromosomal instability across the whole genome. According to the receiver operating characteristic curve and the statistical distribution, CIN score exceed 3881 was defined as “High”. 32 (53.3%) patients with high CIN score had similar clinicopathologic characteristics compared with low CIN score patients. The median overall survival of patients with high CIN score was 21.2 months (95% CI 14.1–28.3), which was significantly inferior to those with low CIN score (not reached, P = 0.006). Regardless of various treatment regimens, the median progression free survival in patients with high CIN score was 7.3 months, which was significantly worse than those in the low CIN score population (11.0 months, P = 0.034). Multivariate analysis revealed that CIN score was an independent prognostic factor, with hazard ratio of 3.563 (P = 0.005). Conclusions: To our knowledge, this is the first study illustrating the prognostic value of chromosomal instability derived from cfDNA in MBC.